1959
DOI: 10.1139/v59-118
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Organo-Phosphorus Compounds: Iii. Phosphoramidates, Phosphoramidothionates, and Related Compounds

Abstract: Examination of a number of new phosphorus compounds has provided additional confirmation for many of the group frequencies reported previously. In certain cases additional information has been obtained on the effect of environment on the band positions, and some previously unassigned bands have been attributed to specific structures. In particular, bands previously assigned to P(S), P(S)X, C—H deformation, P—O—(C), P—C, P—S—H, P—S(P), P—N, C—S(P), and C—N(P) are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The results of infrared assays showed that the C=O stretching band appeared at a lower frequency (1781 cm −1 ), confirming CrpP wt activity-induced modification of the carboxylic function. Moreover, the absorption bands observed for CIP incubated in presence of CrpP wt were found to be at the same frequency as known organophosphorus compounds [15,16], suggesting that this could be the reason for the few bands that overlap with CIP. In addition, significant changes such as band intensity and the appearance of new bands in the region from 1000 to 700 cm −1 provided evidence about CIP phosphorylation by CrpP wt .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results of infrared assays showed that the C=O stretching band appeared at a lower frequency (1781 cm −1 ), confirming CrpP wt activity-induced modification of the carboxylic function. Moreover, the absorption bands observed for CIP incubated in presence of CrpP wt were found to be at the same frequency as known organophosphorus compounds [15,16], suggesting that this could be the reason for the few bands that overlap with CIP. In addition, significant changes such as band intensity and the appearance of new bands in the region from 1000 to 700 cm −1 provided evidence about CIP phosphorylation by CrpP wt .…”
Section: Discussionmentioning
confidence: 90%
“…2a), indicating the phosphorylation of CIP by CrpP wt . Phosphorus compounds are known to show absorption bands for P-O-H around 3000-2800 cm −1 and 2400-2200 cm −1 , for P=O(OH) (single OH), 2800-2700 cm −1 , 2400-2300 cm −1 , and 1750-1600 cm −1 broad band [15,16]. At exception of mutation in I26, mutations in Gly7, Asp9, Lys33, and Cys40 in CrpP affect negatively the protein ability to modify the CIP molecule, since the infrared results showed that the -OH and C=O stretching bands remains in the same region at 3100-3000 cm −1 and 1784 cm −1 showing a similar pattern to the CIP without CrpP incubation, (Fig.…”
Section: Conserved Residues Of Crpp Are Important To Cip Modificationmentioning
confidence: 99%
“…This technique permits observation of cyanate species [32] [33] (CN at 2168 cm -1 , Fig. S7a) and phosphates, whether they are free or bonded (to carbamoyl moieties) [34] [35] (PO around 1100 cm -1 , Fig. S6).…”
Section: ) Carbamoyl Phosphate Hydrolysismentioning
confidence: 99%
“…The strong absorption bands measured in the 900-1,300 cm -1 region, with a maximum at approximately 1,100 cm -1 , can be attributed to the P=O bond of the phosphate species [33][34][35]. The band at 990 cm -1 is related to the asymmetric stretching of the P-O-R bond of the organophosphorus compounds, for example, O=P(OR) 3 [35,36]. The two bands appearing at 935 and 740 cm -1 result from the asymmetric and symmetric stretching vibrations of the P-O-P bonds [31,35], which could be attributed to the presence of poly(organo)phosphate compounds.…”
Section: Atr-ftirmentioning
confidence: 99%